Pengaruh Waktu Kontak Karbon Aktif dari Kulit Durian terhadap Kadar COD, BOD, dan TSS pada Limbah Cair Industri Tahu - Lydiana Eka Nabilla; Rusmini Rusmini (Universitas Ahmad Dahlan, 2019)
The disposal of tofu industrial wastewater into the environment without treatment can cause pollution. The purpose of this study was to utilize durian peel as activated carbon which is used to treat the tofu industrial wastewater through adsorption process. In addition, to determine the effect of variation in contact time on the adsorption process. Carbon from durian peel with chemical activation using KOH 25% containing 10.15% water, 6.14% ash, and iod adsorption of 1194.83 mg/g. Activated carbon from durian peel was tested by FTIR obtained by functional groups of –OH, C−H, and C=C aromatic. Porosity analysis of activated carbon using SAA with BET method obtained surface area of 471.6 m2/g, pore volume of 0.5698 cc/g, and average pore diameter of 24 Å classified as mesoporous. Adsorption process between activated carbon and tofu industrial wastewater variations in contact time during 30, 60, 90, and 120 minutes. Based on the study, the optimum contact time was 90 minutes. At that time, activated carbon from durian peel can reduce COD levels to 57%, BOD to 59%, and TSS to 72% from the initial levels of tofu industrial wastewater.